Becoming a helper - Corey, Marianne Schneider (Thomson Higher Education, 2007)
Ideal for anyone embarking on or considering a career in human services, counseling, psychology, social work, or any of the other helping professions, this book provides an overview of the stages of the helping process, as well as the skills and knowledge required to be a successful helping professional. Drawing on their years of experience, the Coreys focus on the struggles, anxieties, and uncertainties one encounters on the road to becoming an effective helper. The book emphasizes self-reflection on a number of professional issues and challenges the reader to examine their motives for choosing a helping career, and takes a candid look at the demands and strains they'll face in the helping professions